2008
DOI: 10.2164/jandrol.107.003194
|View full text |Cite
|
Sign up to set email alerts
|

Factors From Damaged Sperm Affect Its DNA Integrity and Its Ability to Promote Embryo Implantation in Mice

Abstract: Endogenous nucleases in mouse sperm can be activated by freeze-thawing the spermatozoa in media without cryoprotection and cleaving spermatozoa DNA. The role of sperm chromatin integrity during intracytoplasmic sperm injection (ICSI) is of critical importance. We analyzed in the B6D2 mouse the proportion of DNA-fragmented spermatozoa (DFS) produced by incubation in conditioned medium (CM) generated by freeze-thawing sperm in the absence of cryoprotection. We then examined the subsequent development, implantati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 67 publications
(75 reference statements)
3
30
0
1
Order By: Relevance
“…Therefore, detailed observation of embryos derived from pre-treated spermatozoa should be carried out during pre-and post-implantation. The present results revealed that embryos derived from damaged (pre-treated) spermatozoa frequently developed up to the blastocyst stage with active mitosis (Table 2), in agreement with another study (Perez-Crespo et al 2008). However, DNA-damaged spermatozoa reduced blastocyst formation depending on the disintegration level (Ahmadi & Ng 1999a, 1999b.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Therefore, detailed observation of embryos derived from pre-treated spermatozoa should be carried out during pre-and post-implantation. The present results revealed that embryos derived from damaged (pre-treated) spermatozoa frequently developed up to the blastocyst stage with active mitosis (Table 2), in agreement with another study (Perez-Crespo et al 2008). However, DNA-damaged spermatozoa reduced blastocyst formation depending on the disintegration level (Ahmadi & Ng 1999a, 1999b.…”
Section: Discussionsupporting
confidence: 91%
“…Chromosomal damage of pre-treated spermatozoa a number of membrane-damaged spermatozoa, since it is reported that the factor released from the spermatozoa induced DNA nicks (Perez-Crespo et al 2008). Nevertheless, ICSI oocytes with incubated or pre-treated spermatozoa have much higher rates of chromosome damage than that of the control group.…”
Section: Discussionmentioning
confidence: 99%
“…The endogenous sperm nucleases are released from plasma membrane-damaged spermatozoa [44] and activated with divalent cations such as Mg 2+ and Ca 2+ [45]. Furthermore, it has been reported that incubation of spermatozoa with endogenous nuclease released from sperm leads to an increase in the proportion of DNA fragmented spermatozoa [39]. In our study, supplementation with EGTA, a chelating agent for the cations, in the buffer can inhibit the sperm DNA fragmentation and improved embryonic development after ICSI [38].…”
Section: Sperm Chromosomal Normalitysupporting
confidence: 49%
“…It has been reported that DNA-fragmented spermatozoa had adverse affect on in vitro embryonic development [38], where we used the DNA-fragmented sperm caused significantly after freeze-drying. There also reported the impaired embryo implantation and fetus development after ICSI in mice [39,40]. DNA fragmentation in human spermatozoa is one of the causes of failure of embryonic development and pregnancy [41].…”
Section: Sperm Chromosomal Normalitymentioning
confidence: 96%
“…Frozen 235 dolphin spermatozoa were thawed the day of the experiment whereas murine M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 9 spermatozoa were obtained from fresh semen. Murine semen was collected from a total of five 9-month old B6D2F1 mice [33]. Mice were fed ad libitum with a standard diet (Harland Ibérica, Barcelona, Spain) and maintained in a temperature and lightcontrolled room (23 °C; 14 hours light: 10 hours dark).…”
Section: Semen Collection Cryopreservationmentioning
confidence: 99%